F18 Clinical measurement of sit to stand performance in people with huntington's disease: reliability and validity for 30 seconds chair sit to stand test. (16th November 2010) - Khalil, H; van Deursen, R; Quinn, L; Rosser, A; Busse, M
Abstract : Background: People with HD often demonstrate difficulties with transitional movements that may be related to impairments in balance, strength or neuromuscular coordination. The 30s Chair sit to stand test (30s CST) is a test designed to measure the number of chair stands a person can complete in 30s. Aim: This study aimed to examine test-retest reliability and concurrent validity of the 30s CST as a measure of transitional movement ability in people with HD. Methods: Concurrent validity was assessed in the entire cohort (n=12) by comparison with measures of gait (velocity and cadence), balance (Timed up and Go (TUG) and Berg Balance Scale (BBS)), function (Physical Performance Test (PPT)) and disease severity (Total Functional Capacity (TFC) scale). Associations between the tests were examined using Pearson correlations. Reliability was assessed with intra-class correlations (ICC) (3, 3) and 95% limits of agreement, in a sub-group of participants (n=7) who performed the 30s CST test twice with one week between testing. Results: 12 subjects participated in the study (mean±SD, 54.6±15.27 years; 6.2±2 units in TFC scale). The 30s CST was not significantly correlated with TFC but correlations with measures of gait, balance and function were all significant. Velocity Cadence TFC TUG BBS PPT 30s CST Pearson correlation 0.86* 0.73* 0.45 −0.87* 0.85* 0.86* * p<0.01. Test-retest reliability was excellent (ICC=0.99). Variability of scores between the test sessions was small (95% limits of agreement (−0.498 to 1.64)). Conclusion: 30s CST test is a simple measure that evaluates a task commonly impaired in HD. The test was not correlated with TFC; the fact that most subjects scored close to 6 may have influenced this result. The test however, has excellent reliability and concurrent validity with other measures of gait and balance; and therefore, it incorporates multiple domains of physical impairments in HD which makes it an important test to be included in future therapeutic trials.